Market Regulators of Service Spheres Innovative Development as a Tool of Regional Socio-Economic Policy - Pugacheva, Anna S.; Filippova, Viktoriya P.; Kon, Andrei Y.; Dorzhieva, Lyudmila B.; Silchenok, Igor S.; Pugacheva, Natalya B.; Lunev, Alexander N.; Mustafina, Alfiya A. (International Review of Management and Marketing, 2016)
The relevance of the study is conditioned by the innovative development of service spheres as the reduction of territorial social and economic differentiation to the level, due to objective differences of the regions and to balance of their revenue base and expenditure commitments. The service sector is one of the most dynamic and growing segments of regional markets and one of the characteristics of effective socio-economic policy in the region. Innovative development of service spheres as a tool for regional socio-economic policy is aimed at creating of a society of equal opportunities, sustainable increase of citizens’ welfare and reduction of poverty and decrease of population’s differentiation by income level. Market regulators of innovative development of service spheres ensure their sustainable capitalization, which is manifested in the competitiveness’s increase of service spheres and the growth of investment attractiveness of the service spheres. The purpose of the article is to identify the characteristics of the market regulators of innovative development of service spheres as a tool for regional socio-economic policy. A leading approach is the institutional approach that considers market regulators of innovative development of service spheres as mechanisms to ensure the growth of profitability from the assets of the service spheres while simultaneous risks’ diversifying and to apply to improve the citizens’ life quality and meet the needs for public goods. The article presents the mechanisms of expanded reproduction of various forms of capital and the establishment of regional services markets; clarifies the mechanism of capitalization of the service spheres that contribute to maximizing of their assets’ value in the process of socio-economic activities; provides a mechanism for assets’ management in the service sector. The paper submissions will be useful for specialists of Federal and regional authorities, local governments, line ministries, scientists interested in issues of regional economy and management of services. Keywords: Innovative Development, Economic Systems, Regional Market of Services, Regional Economy, Management of Services Sphere. JEL Classifications: C15, F15, H43